Effects of gap width on flow motions around twin-box girders and vortex-induced vibrations. Issue 139 (April 2015) - Laima, Shujin; Li, Hui
Abstract: Twin-box girders are employed in long-span suspension bridges for flutter stability. However, the flow around a twin-box girder is notably complicated. The effects of gap width on the flow characteristics at Re =5.58×10 4 and the vortex-induced vibration (VIV) of a twin-box girder at about Re =1.17×10 4 were experimentally investigated using a sectional model. In the experiments, the gap ratio (defined as the ratio of the width L between two box girders to the central height of the girder D ) varied from 0.855 to 10.260. The flow velocities around the model and the surface pressures of the model were measured during static tests, and the acceleration of sectional model also measured during dynamic tests. In addition, corresponding smoke-wire flow visualization tests were conducted under low wind speeds for the same sectional model. The test results show that all of the pressure characteristics, the aerodynamic force, the Strouhal number, the flow pattern and the VIV are dramatically influenced by the gap width. At a gap ratio of L / D =2.138 (defined as the critical gap ratio), the flow motion around the gap between the upstream and downstream box girders suddenly changes, and an alternate shedding vortex appears. According to vortex shedding pattern of the twin-box girder, the flow can be categorized into three basic patterns: pattern A, vortices alternately shedding behind the downstream box girder when the gap ratio is smaller than the critical gap ratio ( L / D <2.138); pattern B, vortices alternately shedding behind the upstream box girder (in the gap) when the gap ratio is in the moderate range (2.138≤ L / D ≤10.26); and pattern C, vortices freely shedding behind the upstream and downstream box girders when the gap ratio approaches infinity. For the VIVs, the twin-box girder experiences four types of VIV as the gap ratio increases: when L / D <1.710, no VIV occurs; when 1.710≤ L / D ≤2.138, only vertical VIV occurs; when 2.566≤ L / D ≤2.933, both vertical and torsional VIVs occur; and when L / D ≥3.421, only torsional VIV forms.